Decadència i castellanització - Fuster, Joan (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: This article speaks about the presence of the Castillian language in the Valencian society from XVI to XIX centuries. It pays special attention to its influence on drama and preaching.